Reverse micellar extraction of a recombinant cold-adapted AMs8 lipase from the antarctic Pseudomonas fluorescens - Abd. Jalil, Fatin Nur Fauzi Ana (2019)
A moderate yield of a purified enzyme can be achieved by using simple technique of reverse micellar extraction (RME). RME is a liquid-liquid extraction method that uses a surfactant and an organic solvent to extract biomolecules. However, there is a lack of study of` RME in extracting cold-adapted enzyme. Instead of traditional chromatographic purification methods, which are tedious and expensive, RME using the non-ionic surfactant Triton X-100 and toluene is used as an alternative purification technique to purify a recombinant cold- adapted lipase, AMS8. AMS8 lipase was isolated from soil samples of Casey Station, Antarctica and was recombinant expressed in Escherichia coli strain BL21 (DE3) (pET32b/AMS8).Various process parameters were optimized to maximize the activity recovery of AMS8 lipase. The optimal conditions were found to be 50 mM sodium phosphate buffer, pH 7, 0.125 M NaCl, 0.07 M Triton X-100 in toluene at 10°C with the 90 kU lipase unit loaded. Approximately 86% of lipase activity was successfully recovered. Structural analysis of the lipase in a reverse micelle (RM) was performed using an in silico approach. The predicted model of AMS8 lipase was simulated in the Triton-X-100/toluene reverse micelles from 5 to 40°C. The lid 2 covering the active site was slightly opened at 10°C. The secondary structure of AMS8 lipase was most affected in the non- catalytic domain compared to the catalytic domain, with an increased coil conformation. Solvent-accessible surface area and radius of gyration supported the evidence of opening lid AMS8 lipase. Then, to further investigate characteristic of AMS8 lipase in reverse micelles, it was simulated in the different Triton X-100 molecules under optimum conditions. AMS8 lipase in 100 molecules of Triton X-100 reverse micelle gives the most stable form. These results suggest that an AMS8 lipase can be extracted using Triton X-100/toluene micelles at low temperature. This RME approach will be an important tool for the recombinant cold-adapted lipases.